Knowledge, Attitude and Skills on Research among the Undergraduate Students of Janapriya Multiple Campus, Pokhara - Pokhrel, Chet Bahadur (Janapriya Journal of Interdisciplinary Studies, 2024)
Knowledge of research and its practical approaches are highly valued in academic institutions. Undergraduate level of university is the foundational level on which the undergraduates must be trained to research oriented activities. Their knowledge of research, their attitudes, and skills matter a lot in research-oriented activities in their personal and professional lives. The present research was carried out with small sample size of 30 participants with mixed methods. It found that all the participants showed strong affinity towards the research related activities hence they liked and enjoyed the research methodology course enthusiastically. They have claimed to have sound theoretical knowledge on research, good and positive attitudes and fundamental skills on research activities. It has also identified that undergraduates’ knowledge, attitudes and skill are not affected by gender, medium of instruction and the faculty that they belonged to. However, in the focus group discussion, they revealed some problems which they faced during the preparation of the report. They clearly reflected some content related problems such as the topic selection, finding the literature review and avoiding plagiarism as the key impediments in their research report writing process. Extensive practices, reading research articles and attending seminars, and webinars can help the undergraduates a lot in coping up the problems related to research works. Extensive organizational research culture frequent practices and the process of collaborative writing can obviously help them to be better and efficient in preparing the report. Giving the time persistently in research works, determination, and choosing the right research methodology can help them a lot in solving the barrier related to undergraduates’ research works.